2005
DOI: 10.1192/bjp.187.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Family education for people with schizophrenia in Beijing, China

Abstract: Family education on schizophrenia by nurses in China was effective in improving knowledge and promoting improvement in patients' symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 23 publications
6
113
0
4
Order By: Relevance
“…Family psycho-education is well accepted and widely used in the US (Dyck et al, 2002, McFarlane et al, 1995, other Western countries (Sellwood et al, 2001), and mainland China (Guo et al, 2010, Li and Arthur, 2005, Xiong et al, 1994; however, four systematic reviews on clinical trials of family intervention for people with schizophrenia (Asen, 2002, Bustillo et al, 2001, Pharoah et al, 2010 have concluded that this approach to family intervention can only produce a modest effect on family functioning and well-being, particularly in the longer term (e.g., >1 year). The findings of this study also revealed that psycho-education groups may not have a substantial effect on the health outcomes of both patients and their family members at 24 months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Family psycho-education is well accepted and widely used in the US (Dyck et al, 2002, McFarlane et al, 1995, other Western countries (Sellwood et al, 2001), and mainland China (Guo et al, 2010, Li and Arthur, 2005, Xiong et al, 1994; however, four systematic reviews on clinical trials of family intervention for people with schizophrenia (Asen, 2002, Bustillo et al, 2001, Pharoah et al, 2010 have concluded that this approach to family intervention can only produce a modest effect on family functioning and well-being, particularly in the longer term (e.g., >1 year). The findings of this study also revealed that psycho-education groups may not have a substantial effect on the health outcomes of both patients and their family members at 24 months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Based on three clinical trials of family interventions in Chinese people with schizophrenia (Chien et al, 2006, Chien et al, 2008, Li and Arthur, 2005, we estimated that 37 family dyads per intervention were required to provide 80% power(two-sided p<0.05) to detect a difference in family functioning change of 0.6 points with a standard deviation of 1.2, or a difference in change of re-hospitalisation rate of 1 (number of re-admissions over 12 months) with a standard deviation of 0.5, indicating a moderate effect size of 0.48 (i.e., the smallest effect size of the three clinical trials referred to on patient and family functioning, ranging from 0.48-0.60). From 520 family dyads (patient and caregiver) that met the criteria of the study, 135(26.0%) were randomly selected and allocated to the three study groups (i.e., 45 family dyads in each group), with an expected attrition rate of 20%.…”
Section: Sample Size and Estimated Study Powermentioning
confidence: 99%
See 2 more Smart Citations
“…The focus of many prior studies, however, is on interventions for groups other than adolescents, including adults with schizophrenia (Barrowclough et al, 2001;Dyck, Hendryx, Short, Voss, & McFarlane, 2002;Dyck et al, 2000;Farooq et al, 2011;Li & Arthur, 2005), first episode psychosis (Agius, Shah, Ramkisson, Murphy, & Zaman, 2007;Breitborde et al, 2011), or recent-onset schizophrenia (Grawe, Falloon, Widen, & Skogvoll, 2006;Lenior, Dingemans, Linszen, de Haan, & Schene, 2001;Lenior, Dingemans, Schene, Hart, & Linszen, 2002). Studies of siblings of adolescents with schizophrenia also have been limited (Friedrich, Lively, & Rubenstein, 2008).…”
mentioning
confidence: 99%